PENGARUH PERLAKUAN HCl PADA KRISTALINITAS DAN KEMAMPUAN ADSORPSI ZEOLIT ALAM TERHADAP ION Ca2+ - Pardoyo, Pardoyo; Listiana, Listiana; Darmawan, Adi (JURNAL SAINS DAN MATEMATIKA, 2009)
ABSTRACT--It has been done a research to determine  the  influence of hydrochloric acid treatnent to the crystalinity and adsorption capability of natural zeolite to Ca2+ ion.  Activation  process was conducted by refluxing  of  zeolite  with  KMnOa  0.5 M  and HCI  (1:1)  for  4  hours with  temperature of  80"C.  The  various concentration  of HCI  soltrtions  used were 4 M  (AZl),  6 M  (AZZ),8  M  (AZ3)  and l0  M  (AZA). Crstalinity of zeolite  was  identified  by  X-Ray  Diftaction  CXRD) while  the amount of  adsorbed Ca2*  ion was measured  by Atomic  Absorption  Spectroscopy  (AAS).  The activated zeolite was applied  to  adsorb calcium metal  ion  using shaker for  5, 15, 60, 90 dan 120 minutes. The results showed  that the increasing of HCI  concentration for  zeoliteactivation  caused  the  decreasing of  crystallinity  of  NZ,  AZl,  AZ2,  AZ3  wrd AZ1  nunely  100%;  101.10%; 9l.9lo/o;  84.93o/o  and 77  .45o/o  respectively. The adsorption percentage.  of Ca2*  ion  from  conc,entration  originally698 ppm (within  60 minutes)  for NZ,  AZl,  AZ2,  AZ3  and AZ,4 was successively  10.75 Vo;  20.91o/o;  l:4.610/o;19.63% and 24.07o/o.  The results indicated that the decreasing  of  crystallinity  of  zeolite caused  the  increasing of zeolite adsorption ability  to Ca2*  ion.Keywords : zeolite, crystallinity,  adsorption,  ,  Ca2*  ion